Application of Nanometal Oxides In Situ in Nonwoven Polyester Fabric for the Removal of Bacterial Indicators of Pollution from Wastewater - Sohair I. Abou-Elela; Hanan S. Ibrahim; Mohamed M. Kamel; Mohamed Gouda (The Scientific World Journal)
The objective of this study is to investigate and assess the use of in situ deposit nanosilver (nAg2O) or nanocopper oxides (nCuO) into nonwoven polyester fabric (NWPF) as a safe and effective antibacterial filter of pollution from domestic wastewater. The bactericidal effect of both nAg2O and nCuO was examined against Gram-negative bacteria (Escherichia coli, Salmonella typhi) and Gram-positive bacteria (Enterococcus faecalis, Staphylococcus aureus) using agar diffusion disk method. In addition, the capability of nAg2O and nCuO as disinfectants for secondary treated domestic wastewater was investigated as a case study. Transmission electron microscope (TEM) confirmed the formation of nAg2O and nCuO particles with average particle sizes of 15 and 41 nm, respectively. Disk diffusion results showed that nAg2O had a higher bactericidal effect than nCuO. Moreover, the disinfection of secondary treated wastewater using 1.27 mg/cm3 of nAg2O in the nonwoven fabric was capable of hindering 99.6% and 91.7% of total and fecal coliforms within 10 minutes with a residual value of 18 and 15 MPN-index/100 mL, respectively. The residual total and fecal coliform concentrations were far less than that stated in the national and international limits for wastewater reuse in agriculture purpose.